STRUKTUR ORGANISASI DALAM SUATU LEMBAGA PENDIDIKAN - Suci Amanah; Chintya Rahman; Maulana Septedi; Muhammad Hasan Basari (CV. Adiba Aisha Amira, 2025)
This paper discusses the structure of organization in educational institutions in general. The purpose of this study is to describe the definition, function, and importance of organizational structure in managing an educational institution. The method used is literature review by collecting data from books and journals related to education management. The results show that organizational structure is essential to define roles, authority, communication flow, and coordination among members of the institution. A well-structured organization contributes to the achievement of educational goals, decision-making effectiveness, and institutional development.